Propostas de melhoria para o PDP de uma empresa de máquinas agrícolas com base no modelo de PDP da Toyota - Corrêa, Fábio Chencci (Universidade Federal de São Carlos, 2007)
While in the last years Toyota Production System (TPS) has been largely studied and documented, Toyota Product Development System (TPDS) remains obscure, although it is known that a good production system hadly depends on a good product development system. This research presents a set of proposals for Product Development Process (PDP) improvement in an agricultural machines company, based in the Toyota s product development principles and practices. For so much, at first it has been made a literature review which objective was to understand and to describe Toyota s PDP and its leading principles from a systemic viewpoint. The research development makes use of action research method to report the study object current situation and raising its main problems, which consist in the target to be hit by the improvement proposals. Such proposals were formatted considering the Toyota s PDP principles and management practices applicability to the studied company reality and its both market and technological context. The work contributes from the academic viewpoint to a better understanding of TPDS and also from the organizational viewpoint about how it is possible to apply the studied principles as the base for reorganization and continuous improvement of an agricultural machines company s PDP
Keywords: Processo de desenvolvimento de produtos; Melhoria contínua; Sistema Toyota de desenvolvimento de produto; Máquinas agrícolas; ENGENHARIAS::ENGENHARIA DE PRODUCAO